Long Term Effects of Organic and Inorganic Fertilizers on Rice under Rice-Wheat Cropping Sequence - Khadka, Yagya Gajadhar; Rai, Suresh Kumar; Raut, Sambhu (Nepal Journal of Science and Technology, 2010)
A long term field experiment was started in 1989 on alluvial soil of Inceptisol at Agronomy Research Farm, Khumaltar, Lalitpur to evaluate the effects of organic and inorganic fertilizers on soil properties and yields of rice under ricewheat cropping sequence. Rice yield was monitored from 1998 to 2003. Chianung-242 rice variety was used as a test crop for all of the five years of experimentation. All the treatments manifested significant increase in rice yield over control. Results showed highest significant grain yield of 7.9 tons ha-1 from the sole application of farmyard manure (FYM) @ 10 tons ha-1. The long-term experiment exhibited that the balanced application of chemical fertilizers alone did not sustain soil productivity under continuous cropping system. Application of 100 kg N ha-1 alone produced the yield up to 7.2 tons ha-1 whereas phosphorus and potassium did not affect the yields in most of the years. None of the soil properties, soil pH, organic carbon, total nitrogen, available phosphorus and potassium were affected by application of balanced fertilizers while with the application of 10 tons FYM ha-1, the total nitrogen, available phosphorus and organic carbon contents in the soil were improved as compared to other treatments. The efficiency of fertilizers and manure was influenced by the amount of rainfall received as reflected by the higher grain yield during the higher rainfall years. Key words: rice, alluvial soil, organic manure, inorganic fertilizers, rice-wheat system DOI: 10.3126/njst.v9i0.3156 Nepal Journal of Science and Technology 9 (2008) 7-13